Determination of antioxidant activity, total phenolic and total flavonoid contents in tamarillo (Solanum betaceum) peel's ethanolic extracts - Silitonga, Desni Rinanda; Arianto, Anayanti; Silalahi, Jansen (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Free radicals are chemical species a molecule, atom with unpaired electrons and reactive as oxidizing agent which cause oxidize stress in tissue. Antioxidants are substances that can protect cells from free radicals by releasing electrons to neutralize free radicals. Tamarillo peel contains phenolic and flavonoid compounds which have antioxidant activity. The aim of this study was to determine the antioxidant activity, total phenolic and flavonoid content of the ethanol extract of tamarillo peel. Methods: In this research, the maceration method was used to extract phenolic and flavonoid components from tamarillo peel with ethanol 70% solvent. Total phenolic and flavonoid content was determined with UV-vis spectrophotometer. Total phenolic content determined using the Folin-Ciocalteu reagent and expressed in GAE (Garlic acid equivalent) and the total flavonoid content used the AlCl-3 reagent and expressed in QE (Quersetin equivalent). Then, tamarillo peel ethanol extract was tested the antioxidant activity using the DPPH method. Result: The results showed that the total polyphenol content was 66.6242 mg GAE/g extract or 6.66% w/v extract, total flavonoid content was 0.74246 % w/v or 7.4246 mg QE/g extract. Antioxidant activity in IC50 value was 47.9460 ppm. Conclusions: From the results of the research conducted, it can be seen that the ethanol extract of tamarillo can provide an antioxidant effect in the very strong category.